2006
DOI: 10.1523/jneurosci.4441-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Fornix Lesions Decouple the Induction of Hippocampal Arc Transcription from Behavior But Not Plasticity

Abstract: The immediate-early gene (IEG) Arc is transcribed after behavioral and physiological treatments that induce synaptic plasticity and is implicated in memory consolidation. The relative contributions of neuronal activity and learning-related plasticity to the behavioral induction of Arc remain to be defined. To differentiate the contributions of each, we assessed the induction of Arc transcription in rats with fornix lesions that impair hippocampal learning yet leave cortical connectivity and neuronal firing ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 46 publications
5
37
0
Order By: Relevance
“…Cold Spring Harbor Laboratory Press on May 10, 2018 -Published by learnmem.cshlp.org Downloaded from likely to have impaired the stable maintenance of IA traininginduced LTP. Such IA-associated LTP within area CA1 is widely distributed (Whitlock et al 2006), consistent with theoretical and previous experimental mapping studies suggesting that IA and other forms of learning engage widely distributed neural circuits throughout hippocampus (Buzsaki et al 1990;Treves and Rolls 1994;Guzowski et al 1999;Taubenfeld et al 2001;de Hoz et al 2005;Fletcher et al 2006). Our experiments here showing that the maintenance of LTP was impaired up to ∼1200 µm from the site of the inhibitor infusion suggest that acute interference with synaptic plasticity mechanisms over a spatially limited extent within dorsal hippocampus has significant effects on behavioral performance.…”
Section: Discussionsupporting
confidence: 89%
“…Cold Spring Harbor Laboratory Press on May 10, 2018 -Published by learnmem.cshlp.org Downloaded from likely to have impaired the stable maintenance of IA traininginduced LTP. Such IA-associated LTP within area CA1 is widely distributed (Whitlock et al 2006), consistent with theoretical and previous experimental mapping studies suggesting that IA and other forms of learning engage widely distributed neural circuits throughout hippocampus (Buzsaki et al 1990;Treves and Rolls 1994;Guzowski et al 1999;Taubenfeld et al 2001;de Hoz et al 2005;Fletcher et al 2006). Our experiments here showing that the maintenance of LTP was impaired up to ∼1200 µm from the site of the inhibitor infusion suggest that acute interference with synaptic plasticity mechanisms over a spatially limited extent within dorsal hippocampus has significant effects on behavioral performance.…”
Section: Discussionsupporting
confidence: 89%
“…With respect to gene function, a number of IEGs that may be importantly involved in both synaptic plasticity and memory have now been identified (Guzowski, 2002). Among these, Arc (activityregulated cytoskeletal-associated protein) has received considerable recent attention (Bramham et al, 2010;Shepherd and Bear, 2011), in part because it is more tightly coupled to the induction of synaptic plasticity than to neuronal activity per se (Fletcher et al, 2006). Importantly, Arc is one of the only IEGs whose mRNA is rapidly transported to activated synaptic zones, where it undergoes local protein synthesis and associates with dendritic cytoskeletal proteins (Link et al, 1995;Lyford et al, 1995;Steward et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Arc is one of the only IEGs whose mRNA is rapidly transported to activated synaptic zones, where it undergoes local protein synthesis and associates with dendritic cytoskeletal proteins (Link et al, 1995;Lyford et al, 1995;Steward et al, 1998). Moreover, Arc expression in hippocampus is rapidly and robustly enhanced following a number of behavioral manipulations, including novel environment exploration and spatial learning (Guzowski et al, 2001;Kelly and Deadwyler, 2002;Fletcher et al, 2006), while inhibiting hippocampal Arc translation with antisense oligodeoxynucleotides (ODNs) blocks both late-phase LTP and the consolidation of some forms of memory in both the hippocampus and amygdala (Guzowski et al, 2000;Ploski et al, 2008); similar patterns of physiological and behavioral data are observed in Arc knock-out mice .…”
Section: Introductionmentioning
confidence: 99%
“…Although memory consolidation requires expression of immediate early genes like Arc (10,(13)(14)(15), it is unknown if Arc is required for plasticity in cortical regions that lack stimulus-induced activity. Although Arc expression has been observed with high levels of neuronal activity (16)(17)(18)(19)(20)(21), such activity is not always sufficient (22)(23)(24). Direct tests linking Arc expression to neural activity require control over neural activity in a topographically specific manner, or a simultaneous assessment of action potential activity and Arc expression on a neuron-byneuron basis.…”
mentioning
confidence: 99%